Semantic scene completion via semantic-aware guidance and interactive refinement transformer - Xiao, Haihong (2025)
Predicting per-voxel occupancy status and corresponding semantic labels in 3D scenes is pivotal to 3D intelligent perception in autonomous driving. In this paper, we propose a novel semantic scene completion framework that can generate complete 3D volumetric semantics from a single image at a low cost. To the best of our knowledge, this is the first endeavor specifically aimed at mitigating the negative impacts of incorrect voxel query proposals caused by erroneous depth estimates and enhancing interactions for positive ones in camera-based semantic scene completion tasks. Specifically, we present a straightforward yet effective Semantic-aware Guided (SAG) module, which seamlessly integrates with task-related semantic priors to facilitate effective interactions between image features and voxel query proposals in a plug-and-play manner. Furthermore, we introduce a set of learnable object queries to better perceive objects within the scene. Building on this, we propose an Interactive Refinement Transformer (IRT) block, which iteratively updates voxel query proposals to enhance the perception of semantics and objects within the scene by leveraging the interaction between object queries and voxel queries through query-to-query cross-attention. Extensive experiments demonstrate that our method outperforms existing state-of-the-art approaches, achieving overall improvements of 0.30 and 2.74 in mIoU metric on the SemanticKITTI and SSCBench-KITTI-360 validation datasets, respectively, while also showing superior performance in the aspect of small object generation.